The Learning Organization from an Islamic Perspective: A Case Study in Islamic Organization - Aini, Ahmad; Burgoyne, John; Weir, David (2010)
“Learning organization” is one of the famous organizational theories and approaches to organizational development and empirical researches have been done on its implementation and application in various sectors and cultural settings. This paper explores the concept of learning organization from an Islamic perspective following an interest in applying the concept in all types of organization. A case study method is used involving two established Islamic organizations in Malaysia. The main source of data is obtained from semi structured interviews which is based on four understanding of learning organization proposed by Ortenblad (2002). The finding shows that there are elements in Islamic management principles practiced in organizations under study that are in congruent with the concept of learning organizations.